An exploration of physics envy with implications for desiderata of psychology theories - Trafimow, David; Fiedler, Klaus (The American psychologist, 2024)
There is a trepidation, anxiety, or intuition, which has persisted for more than a century, that psychology theories are less anchored in fundamental laws than physics theories. Rather than attempt to refute the concern, the present work accepts it and tries out candidate explanations. These pertain to empirical laws, parsimony, scope, reductionism, falsifiability, mathematical operations (multiplication vs. addition), internal coherence, ceteris paribus stipulations, and purposeful omission of relevant factors (idealization). The conceptions underlying these explanations are not strictly independent, but they point to different distinctive features that might account for the unequal status of physics and psychological science and to different means of improving contemporary psychology. Although the available evidence for or against these candidate explanations is scarce and relies mainly on a few telling examples, we conclude that the last of our candidate explanations—reliance on idealized universes—works best and leads to the most insights about what psychology might learn from physics and what research strategies might foster the ideal of theory-driven psychological science in the future. (PsycInfo Database Record (c) 2025 APA, all rights reserved)
Gesehen am 12.06.2025